ISOLATION, IDENTIFICATION, AND ANTIOXIDANT ACTIVITY OF CHEMICAL COMPOUND IN ETHANOL EXTRACT OF PAPAYA LEAVES (CARICA PAPAYA L.) - FARIDA, YUNAHARA; ISWAHYUNI, ISWAHYUNI (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: The purpose of this research was to isolate and identify the active antioxidant compound in ethanol extract of papaya leaves (Carica papaya L.). Methods: The methods used were fractionation using vacuum liquid chromatography (VLC), and the active fraction was purified using column chromatography (CC). The pure isolate was obtained with preparative thin-layer chromatographic (TLC) identified by spectroscopy. Its antioxidant activity was evaluated using 2,2-diphenyl-picryl-hydrazyl. The presence of phenols was analyzed using ultraviolet (UV)-visible, Fourier-transform infrared (FTIR), and gas chromatography (GC)â€“mass spectrometry (MS). Results: The results showed that ethanol extract of papaya leaf has a strong antioxidant activity with IC50 value of 100.0Â±0.07 ppm. The result of VLC fractionation using mobile phase of chloroform-methanol indicated that the active fraction was EtOH.3 that has antioxidant activity with IC50 of 121.6Â±0.66 ppm. The purification using CC produced active fraction EtOH.3.3 with IC50 value of 176.4Â±0.76 ppm. After identified, the active isolate compound EtOH.3.3.1 from preparative TLC, the results of UV-visible spectrophotometry, FTIR spectrophotometry, and GCâ€“MS show the presence of the phenol compounds. Conclusion: The ethanol extract has antioxidant activity and the extract was suspected to contain 2-methoxy-4-vinylphenol compound.